2021
DOI: 10.1002/ejhf.2326
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID‐19 with impaired endothelial glycocalyx, vascular function and myocardial deformation 4 months after infection

Abstract: SARS-CoV-2 infection may lead to endothelial and vascular dysfunction. We investigated alterations of arterial stiffness, endothelial coronary and myocardial function markers 4 months after COVID-19 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 38 publications
6
115
1
4
Order By: Relevance
“…Particularly with respect to neuroinflammatory processes, a study that appeared recently on a preprint server, including 56 patients with persisting neurological deficits for more than 6 weeks after acute SARS-CoV-2 infection, showed a reduced effector molecule expression in memory T cells, which was significantly associated with the severity of cognitive impairment. 73 In addition, prolonged endothelial dysfunction and vascular inflammation have also been linked to ‘long-COVID’ syndrome, 74 , 75 albeit 18 F-FDG PET studies have not revealed areas of brain hypermetabolism, as would be expected in the case of unabating brain inflammation. 59 , 60 Crucially, ongoing blood–brain barrier dysfunction, as well as a prolonged hypercoagulable state that could precipitate cerebrovascular disease and hypoxic–ischemic neuronal injury, may also be implicated in neurological manifestations of ‘long-COVID’.…”
Section: Pathophysiological Mechanisms Underlying Neurological Manife...mentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly with respect to neuroinflammatory processes, a study that appeared recently on a preprint server, including 56 patients with persisting neurological deficits for more than 6 weeks after acute SARS-CoV-2 infection, showed a reduced effector molecule expression in memory T cells, which was significantly associated with the severity of cognitive impairment. 73 In addition, prolonged endothelial dysfunction and vascular inflammation have also been linked to ‘long-COVID’ syndrome, 74 , 75 albeit 18 F-FDG PET studies have not revealed areas of brain hypermetabolism, as would be expected in the case of unabating brain inflammation. 59 , 60 Crucially, ongoing blood–brain barrier dysfunction, as well as a prolonged hypercoagulable state that could precipitate cerebrovascular disease and hypoxic–ischemic neuronal injury, may also be implicated in neurological manifestations of ‘long-COVID’.…”
Section: Pathophysiological Mechanisms Underlying Neurological Manife...mentioning
confidence: 99%
“…Notably, a recent case-control prospective study reported an independent association between SARS-CoV-2 infection, oxidative stress, and endothelial/vascular dysfunction, which was associated with impaired cardiac performance and persistence of COVID-related symptoms 4 months after COVID-19 infection. 75 To date, however, there are no available data in ‘long-COVID’ patients with neurological symptoms in support of these hypotheses.…”
Section: Pathophysiological Mechanisms Underlying Neurological Manife...mentioning
confidence: 99%
“…Recent studies have reported endothelial dysfunction in patients with COVID-19 and convalescent survivors reflected by reduced brachial artery flow-mediated dilation (FMD) in response to hyperemia, which is a non-invasive method to assess systemic vascular endothelial function (11)(12)(13)(14)(15). However, these studies have been limited by their short interval between diagnosis and follow-up ranging from 23 to 120 days.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for acute and persisting subclinical LV dysfunction is unknown, however MRI findings suggest adverse remodeling after myocarditis that may be detected by strain imaging. Another possible mechanism is endothelial and vascular dysfunction that causes subclinical LV function impairment that persists after acute COVID 19 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%